2013
DOI: 10.3892/br.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 2 or human herpesvirus 8 infection and prostate cancer risk: A meta-analysis

Abstract: Abstract. Prostate cancer is the second most frequently diagnosed type of cancer and the sixth leading cause of cancer mortality among males worldwide. The aim of this study was to investigate the association between the infection by herpes simplex virus type 2 (HSV-2) or human herpesvirus 8 (HHV-8) and the risk of prostate cancer. A systematic literature search was performed using PubMed, Cochrane Library, Web of Science, Scopus, CNKI and CBM. The association of HSV-2 or HHV-8 infection with the risk of prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
0
14
1
3
Order By: Relevance
“…In one of the first studies to investigate HHV-8 infection and PCa, Hoffman and colleagues (9) observed a positive association between HHV-8 seropositivity and PCa in a series of case-control studies, most notably one conducted among Afro-Caribbean men from Tobago (Table 1). Subsequent studies, however, have observed null and sometimes even suggestive inverse findings between HHV-8 seropositivity and PCa (10-15), particularly those published before the execution of the present study (10-12). Therefore, to further inform the possible relation between HHV-8 infection and PCa, and to investigate the reproducibility of previous suggestive inverse findings, we conducted a case-control study sampled from the placebo arm of the Prostate Cancer Prevention Trial (PCPT).…”
Section: Introductioncontrasting
confidence: 53%
“…In one of the first studies to investigate HHV-8 infection and PCa, Hoffman and colleagues (9) observed a positive association between HHV-8 seropositivity and PCa in a series of case-control studies, most notably one conducted among Afro-Caribbean men from Tobago (Table 1). Subsequent studies, however, have observed null and sometimes even suggestive inverse findings between HHV-8 seropositivity and PCa (10-15), particularly those published before the execution of the present study (10-12). Therefore, to further inform the possible relation between HHV-8 infection and PCa, and to investigate the reproducibility of previous suggestive inverse findings, we conducted a case-control study sampled from the placebo arm of the Prostate Cancer Prevention Trial (PCPT).…”
Section: Introductioncontrasting
confidence: 53%
“…Several epidemiologic studies have suggested possible associations between STIs and CaP [ 17 - 19 ], but the data are inconsistent. A recent meta-analysis suggested that herpes virus type 2 infection is associated with an increased risk of CaP (odds ratio, 1.209; 95% confidence interval [CI], 1.003–1.456) [ 20 ]. However, another meta-analysis showed that men who reported never having had an STI were at increased risk for CaP (summary relative risk [SRR], 1.49; 95% CI, 1.19–1.92), and that men with gonorrheal infection also showed an increased risk of CaP (SRR, 1.20; 95% CI, 1.05–1.37) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is still contradictory since other epidemiological studies could not find same association [ 23 – 25 ]. Therefore, an elaborate and comprehensive demonstration of the association between herpes virus infection and prostate cancer risk is of significance [ 24 ]. Further investigations and large-sample studies are required to and the relationship between herpes virus infection and prostate cancer risk.…”
Section: Discussionmentioning
confidence: 99%